2016
DOI: 10.1126/sciadv.1500875
|View full text |Cite
|
Sign up to set email alerts
|

Circumstellar disks of the most vigorously accreting young stars

Abstract: Subaru-HiCIAO observations on FU Orionis objects revealed asymmetric structures on 102 to 103 AU scales of circumstellar disks and envelopes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
79
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 70 publications
11
79
1
Order By: Relevance
“…In near-infrared scattered-light imaging of disks, spiral arms have been found in both embedded Class 0/I objects surrounded by infalling envelopes (Canovas et al 2015;Liu et al 2016b) and revealed Class II objects (i.e., Herbig and T Tauri stars; Figure 1). While gravitational instability may drive the arms in Class 0/I disks (e.g., Vorobyov & Basu 2005, 2010Dong et al 2016b;Pérez et al 2016;Tobin et al 2016;Meru et al 2017;Tomida et al 2017), which tend to be massive and are fed by infall from the envelope, the origin of the arms detected in Class II disks is unclear.…”
Section: Sample Selection and Statisticsmentioning
confidence: 99%
“…In near-infrared scattered-light imaging of disks, spiral arms have been found in both embedded Class 0/I objects surrounded by infalling envelopes (Canovas et al 2015;Liu et al 2016b) and revealed Class II objects (i.e., Herbig and T Tauri stars; Figure 1). While gravitational instability may drive the arms in Class 0/I disks (e.g., Vorobyov & Basu 2005, 2010Dong et al 2016b;Pérez et al 2016;Tobin et al 2016;Meru et al 2017;Tomida et al 2017), which tend to be massive and are fed by infall from the envelope, the origin of the arms detected in Class II disks is unclear.…”
Section: Sample Selection and Statisticsmentioning
confidence: 99%
“…On the other hand, the previous CO observations have shown that FU Orionis objects may be associated with extended gaseous disk (Kóspál 2011;Hales et al 2015). The high angular resolution near infrared coronagraphic polarization imaging of the previous Subaru-8.2m telescope observations further resolved spiral arm-like patterns and large-scale (>500 au) arcs on the disks of the four FU Orionis objects FU Ori, Z CMa, V1057 Cyg, and V1735 Cyg, which can be explained by the signatures of disk gravitational instability (Liu et al 2016b;Dong et al 2016). However, the CO and infrared emission are both optically thick in the observed regions, and therefore cannot provide good constraints on disk mass distributions.…”
mentioning
confidence: 84%
“…Figure 1 shows the SMA 224 GHz image and the JVLA 33 GHz image, which were generated utilizing the full bandwidth coverages of these observations (Section 2.1.1, 2.2.1). An overlay of the JVLA 33 GHz image with the previous Subaru High Contrast Instrument for the Subaru Next Generation Adaptive Optics (HiCIAO) 1.6 µm polarization intensity image (Liu et al 2016b) is presented in Figure 2. The 33 GHz image resolved two compact emission sources, which are immediately around FU Ori and a projectedly nearby source FU Ori S. They center at R.A. = 05 h 45 m 22 s .368 (J2000), decl.…”
Section: Ghzmentioning
confidence: 99%
See 1 more Smart Citation
“…comm.). In Subaru/HiCIAO H-and K-band scattered-light imaging of four outbursting FU Ori disk systems, Liu et al (2016) displayed a linear feature on a scale of 1000 au at an odd angle with respect to the centre-radial direction (their Fig. 1).…”
Section: Observabilitymentioning
confidence: 99%